(untitled) (Southwestern Research Journal, 2023)
The study examines about the employers who have improved their performance after the training. The main study of this research is how training has done impact on employee performance. When we examine the effect of three sets various independent variables was taken into account and two sets of hypotheses which developed establishing relationship between these set of variables with dependent variables. 200 questionnaires were distributed among employees of several organization of Kathmandu valley and 150 have responded. The data are analyzed in statistical tools of the participants of employees. We surely know that there is positive and significant relationship between training and employee performance. It is a vital role in improving the performance of employees. We known the training regarding employee performance are conducted in various organizations. Training has influencing power on employees work commitment and performance which reinforce and implement training as root of organization to exceed goals. The study concentrates to improve employee performance that is lacking to achieve a task in an organization. It major impacts are to encourage employees to work apparently.